2003
DOI: 10.1164/rccm.200205-420oc
|View full text |Cite
|
Sign up to set email alerts
|

Antiinflammatory Effects of Genistein, a Tyrosine Kinase Inhibitor, on a Guinea Pig Model of Asthma

Abstract: Protein tyrosine kinase signaling cascade plays a pivotal role in the activation of inflammatory cells. The purpose of this study was to investigate the effects of genistein, a broad-spectrum protein tyrosine kinase inhibitor, on airway inflammation in an in vivo guinea pig model of asthma. Guinea pigs were actively sensitized by intraperitoneal injections of ovalbumin. Aerosolized ovalbumin induced acute bronchoconstriction in conscious animals in a dose-dependent manner. Genistein (15 mg/kg given intraperito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(79 citation statements)
references
References 38 publications
5
73
0
1
Order By: Relevance
“…genesis, the possible therapeutic use of a tyrosine kinase inhibitor to treat asthma has been investigated in several studies (Duan et al, 2003Vargaftig and Singer, 2003). Until now other studies have showed that EGFR tyrosine kinase inhibitors have anti-inflammatory effects in asthma model, but can not explain adequate mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…genesis, the possible therapeutic use of a tyrosine kinase inhibitor to treat asthma has been investigated in several studies (Duan et al, 2003Vargaftig and Singer, 2003). Until now other studies have showed that EGFR tyrosine kinase inhibitors have anti-inflammatory effects in asthma model, but can not explain adequate mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Considered a broad-spectrum protein tyrosine kinase inhibitor, genistein (42) (15 mg/kg administered intraperitoneally to sensitized male Hartley guinea pigs) inhibited ovalbumin-induced acute bronchoconstriction and airway hyperresponsiveness to methacholine, eosinophilic inflammation both in BALF and in airways and eosinophil peroxidase activity in cell-free assays. The authors suggested that the inhibition of the tyrosine signaling cascade by via genistein (42) stimulus may present a therapeutic possibility for allergic airway diseases [122].…”
Section: Asthmamentioning
confidence: 99%
“…In mice, injection of genistein caused a decrease in relative percentages of both thymic CD4(+)CD8()) and CD4(+)CD8(+) thymocytes (39,45). As genistein is an inhibitor of tyrosine kinase -an enzyme playing a pivotal role in the activation of inflammatory cells, it has been proposed that soy isoflavones have immunosuppressive and antiinflammatory properties (78)(79)(80). However, a few experimental data does not correspond with this assumption.…”
Section: Phytoestrogens Gender and Allergic Responsementioning
confidence: 99%
“…Daidzein exerted a stimulatory effect on nonspecific immunity, as shown by enhancement in the phagocytic response of peritoneal mice macrophages and thymus weight (43). Studies on an guinea-pig model of asthma demonstrated that genistein, contrary to daidzein, which has no inhibitory activity against tyrosine kinases, effectively reduced acute bronchoconstriction, pulmonary eosinophilia, and AHR induced by ovalbumine (OVA), but not histamine or metacholine (79). However, other results show that the reduction of antigen-induced eosinophilia in the lung of the asthmatic guinea-pigs being on a diet enriched with isoflavones is accompanied by a potentially detrimental increase in antigen-induced leakage of protein into the airspace (78).…”
Section: Phytoestrogens Gender and Allergic Responsementioning
confidence: 99%